2021
DOI: 10.1101/2021.02.09.430450
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Unit Pipe Pneumatic model to simulate gas kinetics during measurements of embolism in excised angiosperm xylem

Abstract: The Pneumatic method has been introduced to quantify embolism resistance in plant xylem of various organs. Despite striking similarity in vulnerability curves between the Pneumatic and hydraulic methods, a modeling approach is highly needed to demonstrate that xylem embolism resistance can be accurately quantified based on gas diffusion kinetics. A Unit Pipe Pneumatic (UPPn) model was developed to estimate gas diffusion from intact conduits, which were axially interconnected by interconduit pit membranes. The… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…Relatively fast Effervescence; vessel length exceeds cavitation chamber length; hydraulic artefacts; destructive Cochard et al, 1992;Gullo and Salleo, 1992;Yin and Cai, 2018 Pereira et al, 2016Pereira et al, , 2020aBittencourt et al, 2018;Zhang et al, 2018;Paligi et al, 2021;Yang et al, 2021 (Schenk et al, 2020), xylem sap will come out at the cut-open end, which will not only be problematic for pneumatic measurements, but also for hydraulic methods. Other forms of wounding response are likely slow and unlikely to affect the vessel dimensions during dehydration.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Relatively fast Effervescence; vessel length exceeds cavitation chamber length; hydraulic artefacts; destructive Cochard et al, 1992;Gullo and Salleo, 1992;Yin and Cai, 2018 Pereira et al, 2016Pereira et al, , 2020aBittencourt et al, 2018;Zhang et al, 2018;Paligi et al, 2021;Yang et al, 2021 (Schenk et al, 2020), xylem sap will come out at the cut-open end, which will not only be problematic for pneumatic measurements, but also for hydraulic methods. Other forms of wounding response are likely slow and unlikely to affect the vessel dimensions during dehydration.…”
Section: Discussionmentioning
confidence: 99%
“…The removal of incorrect Ψ 50 values in the above references considerably improves the correlation between P 50 values based on the pneumatic method and other methods. Moreover, the Unit Pipe Pneumatic model indicates that 91% of the gas volume extracted in 15 s of simulation comes from the first two series of intact and embolised vessels, while only 9% of the gas extracted results from xylem sap ( Yang et al, 2021 ), which is saturated or supersaturated with gas ( Schenk et al, 2016 ). This modelling exercise also showed that the Pneumatron may underestimate embolism resistance by 2–17%, with a typical measuring error of 0.11 MPa for Ψ 50 values.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations